2018
DOI: 10.3390/geriatrics3030036
|View full text |Cite
|
Sign up to set email alerts
|

A Stab in the Dark: A Case Report of an Atypical Presentation of Giant Cell Arteritis (GCA)

Abstract: Background: Giant cell arteritis/temporal arteritis (GCA) is an inflammatory condition that affects large to medium vessels such as the aorta and its primary branches. Patients classically present with fatigue, fever, headache, jaw claudication and in severe cases, may suffer either transient (amaurosis fugax) or permanent visual loss. The reference standard for diagnosis is the temporal artery biopsy (TAB) and the mainstay of treatment is with immunosuppression. Our patient JG, presented with a range of non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Next, considering hospital-acquired infections, such as Pseudomonas aeruginosa , the patient was changed to tazobactam/piperacillin, but no response was observed. Blood culture results were also negative, and the possibility of infection was ruled out [ 7 ]. The condition was progressive, and contrast-enhanced CT findings showed thickening of the wall of the aortic arch, so treatment with prednisolone was started, considering the possibility of giant cell arteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Next, considering hospital-acquired infections, such as Pseudomonas aeruginosa , the patient was changed to tazobactam/piperacillin, but no response was observed. Blood culture results were also negative, and the possibility of infection was ruled out [ 7 ]. The condition was progressive, and contrast-enhanced CT findings showed thickening of the wall of the aortic arch, so treatment with prednisolone was started, considering the possibility of giant cell arteritis.…”
Section: Discussionmentioning
confidence: 99%
“…PMR patients with atypical features, which include inflammatory-type lower back pain, predominant pelvic girdle discomfort or lower limb pain, severe systemic symptoms and poor response to moderately dosed steroids, were more likely to have concurrent LVV and therefore should be investigated as such 39. One study recommended screening for LVV in all elderly patients with non-specific symptoms and biochemical evidence of systemic inflammation (elevated CRP, ESR or platelets) 40. An extension of this concept was also depicted by Chan et al in a retrospective audit, which suggested that the combination of high CRP and thrombocytosis demonstrated high sensitivity and specificity for GCA and possibly a better diagnostic yield for the condition than isolated elevations in CRP or ESR (figure 3).…”
Section: Discussionmentioning
confidence: 99%